Engineering cell microenvironment using novel functional hydrogels - Zhang, X.; Liu, M.; Li, Y.; Dong, Y.; Pingguan-Murphy, Belinda; Lu, T.J.; Xu, F. (Elsevier, 2015)
Cell microenvironment plays critical roles in regulating cellular activities both spatially and temporally. Engineering cell microenvironment using hydrogels has attracted increasing attention given their native-mimicking properties. In particular, developing hydrogels with specific functions has recently emerged as novel biocomposites to enable the regulation of cell microenvironment from a variety of aspects such as the biological, mechanical and electrical microenvironment. In this review, the state-of-the-art methods for the preparation and application of several novel functional hydrogels are presented, including magnetic hydrogels, photoresponsive hydrogels, conductive hydrogels, thermoresponsive hydrogels, molecule-response hydrogels, as well as tough and stretchable hydrogels. In particular, the applications of these functional hydrogels for engineering cell microenvironment are also reviewed. Concluding remarks and perspectives for the future development of functional hydrogels are addressed.